Molecular Regulation of Histamine Synthesis - Huang, Hua; Li, Yapeng; Liang, Jinyi; Finkelman, Fred D. (Frontiers in Immunology, 2018)
Histamine is a critical mediator of IgE/mast cell-mediated anaphylaxis, a neurotransmitter and a regulator of gastric acid secretion. Histamine is a monoamine synthesized from the amino acid histidine through a reaction catalyzed by the enzyme histidine decarboxylase (HDC), which removes carboxyl group from histidine. Despite the importance of histamine, transcriptional regulation of HDC gene expression in mammals is still poorly understood. In this Review, we focus on discussing advances in the understanding of molecular regulation of mammalian histamine synthesis.